Pemanfaatan Reels Instagram Untuk Meningkatkan Fungsi Informasi di Perpustakaan PEVITA - Nurhayati, Anna; Ria Dyan Rahayu (Jurnal IPI (Ikatan Pustakawan Indonesia), 2023)
The function of library information has the meaning of a library as a place for providing all kinds of information in various forms and formats. The current information society raises the behavior of seeking information with various technological media. This article is the result of action research with 2 cycles on the use of Instagram reels to improve the function of library information on the @pevita library account. Collecting data using questionnaires, observations and interviews. This action research data analysis is descriptive qualitative and quantitative. The results showed that the use of Instagram reels was considered effective in improving the information function of the PEVITA library. Cycle 1 shows 76% of respondents agree, and in cycle 2 it increases to 86%. The strategies used by librarians in utilizing these reels are to: (1) carry out initial coordination with the core social media team; (2) determine content; (3) implementation of content creation; (4) monitoring and evaluation.